Representamos fracciones equivalentes - Benavides Rangel, Gregorio (2020)
The purpose of this proficiency work is to promote meaningful learning related to solving quantity problems through the equivalent fractions in students in the fourth grade "A" of primary education._x000D_ The learning session corresponds to the area of mathematics and was developed following the recommendations of the problem-solving approach, which has been proposed by the Ministry of Education. It has also taken into account the pedagogical and didactic processes necessary to achieve the learning of the competition solves quantity problems._x000D_ Teaching and learning strategies were used to promote the active and meaningful participation of all students._x000D_ The learning session will be evaluated through a checklist to assess performance achievement